Syirkah al-Wujūh Perspektif Mazhab Syafii dan Mazhab Hambali: Syirkah al-Wujūh from the Perspective of the Shafi'i and Hanbali Schools of Thought - Muttazimah, Muttazimah; Kurnaemi Anita; Nur Ismi Auliah (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, IndonesiaInstitut Agama Islam STIBA Makassar, Indonesia, 2025)
Syirkah al-Wujūh is a partnership contract between two individuals who do not possess capital but rely on their social reputation and credibility in the community. This study aims to understand the concept of syirkah al-wujūh from the perspectives of the Shafi'i and Hanbali schools and to determine which opinion is more authoritative between them. This research employs a qualitative descriptive approach (non-statistical), focusing on the study of textual sources using normative and comparative approaches. It examines various aspects by relying on secondary sources from the Qur’an, Hadith, and the views of scholars in fiqh literature discussing syirkah al-wujūh. The findings of this research are as follows: First, according to the Shafi'i school, syirkah al-wujūh is a cooperation contract between two parties who share the profits obtained from purchasing goods based on their social reputation. Meanwhile, the Hanbali school defines syirkah al-wujūh as a partnership between two or more individuals who share profits from goods purchased on a deferred payment basis, relying on their social credibility. Second, the two schools differ in their interpretation of the syirkah al-wujūh contract, leading to different legal rulings regarding its validity. The stronger opinion between the two ultimately refers to the general legislation on syirkah, as there is no explicit evidence permitting or prohibiting specific forms of syirkah, including syirkah al-wujūh. The implication of this research is that it can serve as a reference for resolving community issues related to syirkah al-wujūh and as a guideline for entrepreneurs or business practitioners facing similar situations.